2003
DOI: 10.21273/horttech.13.1.0103
|View full text |Cite
|
Sign up to set email alerts
|

Fertigation Uniformity Affected by Injector Type

Abstract: Application uniformity of fertilizers and pesticides is critical for crop uniformity, but can be difficult to determine when a fertilizer or chemical (fertigation/chemigation) is applied via drip irrigation or deep irrigation tape. Three injectors (venturi, pump, and proportional) were compared in a greenhouse experiment with a continuous-injecting experimental plot injector for fertilizer distribution uniformity in a drip irrigation system. Injection rate and solution volume were evaluated in a field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 0 publications
0
9
0
2
Order By: Relevance
“…Bracy et al . () also obtained better fertilizer distribution with the Venturi injector and proportional pump compared with the continuously diluting injector in greenhouse experiments.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Bracy et al . () also obtained better fertilizer distribution with the Venturi injector and proportional pump compared with the continuously diluting injector in greenhouse experiments.…”
Section: Introductionmentioning
confidence: 82%
“…Bracy et al . () found that injection rates resulting from various pressure differences had a more significant impact on fertigation uniformity than injector type, and the uniformity of fertilizer distribution in the field was greater with a low injection rate than that with a higher injection rate.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nutrient distribution uniformity through drip irrigation mainly depends on system operating pressure, fertilizer type, injection device, length of lateral and dripper type (Santos et al, 1997;Imas, 1999;Patel and Rajput, 2000;Jiusheng et al, 2007;Kumar et al, 2012Kumar et al, , 2014. The urea fertilizer distribution uniformity decreased with increase in drip-line length, however it increased with increase in the operating pressure (Townsend, 1988;Bracy et al, 2003;Kumar et al, 2014). Venturi is the most commonly used device for fertilizer injection through drip irrigation (Bucks and Nakayama, 1980;Nakayama and Bucks, 1986;Sivanappan et al, 1987;Ah Koon et al, 1990;Hanson et al, 1997;Prasad, 1997;Li, and Rao, 2003;Abdallah EL-Amin et al, 2006;Jiusheng et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Bracy et al (2003) explored the relationship between type of injector and fertigation uniformity, concluding that the type of crop and its water and nutrient needs dictate the best injector. Li et al (2007) conducted similar tests and recommended injectors that provide a constant rate of injection in order to provide uniform fertilizer distribution.…”
Section: Introductionmentioning
confidence: 99%